Pembelajaran Tutor Sebaya Dalam Upaya Meningkatkan Hasil Belajar Matematika Materi Operasi Hitung Bilangan Bulat Pada Siswa Kelas VI SDN 1 Sumberejo, Kemiling, Bandar Lampung - Sarifah, Sarifah (LPPM STKIP PGRI Bandar Lampung, 2021)
One of the goals of learning mathematics in elementary school is to train thinking and reasoning in drawing conclusions, for example through investigation, exploration, experimentation, showing similarities, differences, consistent and inconsistent and developing creative activities that involve imagination, intuition, and discovery. by developing divergent thinking, originality, curiosity, making predictions and guesses, experimenting and problem solving skills. Based on the reflection of the sixth grade teacher at SDN 1 Sumberejo Kemiling, teachers often use the lecture method and assign assignments. Teachers have not used innovative and creative approaches, methods, or learning models. This causes students to be less enthusiastic about learning mathematics because they are only passive learning objects and only do the tasks given by the teacher. Problem solving used in this research is to apply peer tutor learning methods. This research is a classroom action research which consists of 3 cycles. The research subjects were teachers (researchers) and sixth grade students at SDN 1 Sumberejo Kemiling Bandar Lampung with a total of 28 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that: (1) classical student learning completeness increased from 35.7% in the pre-cycle to 57.1% in the first cycle, increased again to 85% in the second cycle and increased to 89.3%. The data has reached the established success indicators of 75%; (2) The average score of the students' formative tests increased from 52.86 in the pre-cycle stage to 59.64 in the first cycle; increased to 66.43 in the second cycle; and again increased to 76.79 in cycle III. The data has reached the indicators of research success, namely the average score of individual students 60; (3) The number of students who scored above the KKM has also increased. At the pre-cycle stage as many as 10 students or 35.7%, increased in the first cycle to 16 students or 57.1%; experienced an increase in the second cycle to 20 students or 71.4%; and again increased in the third cycle to 25 students or 89.3% The data has reached the indicator of research success, namely the number of students who scored above the KKM by 75% The conclusion from this peer research is that through the implementation of the tutor method, it can improve the quality of mathematics learning in integer arithmetic operations for sixth grade students at SDN 1 Sumberejo Kemiling Bandar Lampung in the 2018/2019 school year. Suggestions from researchers are (1) creating a harmonious and pleasant atmosphere so that it can motivate students to be active in developing their abilities; (2) Teachers can apply peer tutoring methods as an alternative to improve the quality of teacher teaching in a lesson, especially in learning mathematics.